(3QSGdI aj GdJTjYs - (3GdYGedj, YR GdOjf, GdMSjf Hf YHO GdUeO Hf eMeO GdLHYj, J (B984(3g` (B1576(3es
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg Ydi eG CfYe acai (B... (3hHYO agPg UhQI HMK hbY dgPG GdabjQ Edi QMeI QHg GdZfj (B... (3aj MdH SfI EMOi hNeSjf hJSY eFI CVGafj HYV aVdGFgG (B... (3abdJ dg(B: (3Efg jbHM HeKdj heKdc HYO Cf GfUQa cd YeQgs
(3BNQgG (B:s
(3BNQgG(B: (3Ke HGMKJg aj eSGFd cdGejI cGdQDjI hGdbVGA hGdbOQ haj eSGFd aQYjI cGdeSM hGdeJYI hPdc HYO Cf cGf bO CPYf hGSJbQ GdEjeGf aj bdHg (B... (3hUGQ ef NhGU GdTjYI hddg GdMeO ChdG hBNQG hXGgQG hHGWfGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B2: 240s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3GdJhMjO hGdedd hGdfMds